Hubungan Usia Menarche dan Siklus Mentruasi dengan Dismenore: Hubungan Usia Menarche dan Siklus Mentruasi dengan Dismenore - Elvi Destariyani; Intan Kurnia Apsara; Dwi Yunita Baska (AKADEMI KEBIDANAN DHARMA HUSADA KEDIRI, 2023)
More than 50% of women in every country experience dysmenorrhea. Thus study was to determine the relationship between age of menarche and menstrual cycle with dysmenorrhea ini female student at Bengkulu City. This study has an analytic survey research design with a case cotrol approach. The population is all female student who have menstruated at Bengkulu city with a sample of case 30 cases and 30 controls. Tes data analysis using the chi-square test. The result of the study were that most of the respondents with menarche were< 12 tahun years old and had normal menstrual cycles. There is a relationship between the age of menarche and the occurance of dysmenorrhea p value=0,020 and the menstrual cycle with the occurrence of dysmenorrhea p value = 0,026. It is hoped that UKS officers can provide an explanation of the risk factor for dysmenorrhea and efforts to prevent and manage of dysmenorrhea